Degradation Effects at the Porous Transport Layer/Catalyst Layer Interface in Polymer Electrolyte Membrane Water Electrolyzer. Issue 3 (1st March 2023) - Liu, Chang; Shviro, Meital; Bender, Guido; Gago, Aldo S.; Morawietz, Tobias; Dzara, Michael J.; Biswas, Indro; Gazdzicki, Pawel; Kang, Zhenye; Zaccarine, Sarah F.; Pylypenko, Svitlana; Friedrich, K. Andreas; et al.
Abstract : The porous transport layer (PTL)/catalyst layer (CL) interface plays a crucial role in the achievement of high performance and efficiency in polymer electrolyte membrane water electrolyzers (PEMWEs). This study investigated the effects of the PTL/CL interface on the degradation of membrane electrode assemblies (MEAs) during a 4000 h test, comparing the MEAs assembled with uncoated and Ir-coated Ti PTLs. Our results show that compared to an uncoated PTL/CL interface, an optimized interface formed when using a platinum group metal (PGM) coating, i.e., an iridium layer at the PTL/CL interface, and reduced the degradation of the MEA. The agglomeration and formation of voids and cracks could be found for both MEAs after the long-term test, but the incorporation of an Ir coating on the PTL did not affect the morphology change or oxidation of IrOx in the catalyst layer. In addition, our studies suggest that the ionomer loss and restructuring of the anodic MEA can also be reduced by Ir coating of the PTL/CL interface. Optimization of the PTL/CL interface improves the performance and durability of a PEMWE.